Provably-Secure (Chinese Government) SM2 and Simplified SM2 Key Exchange Protocols - Ang Yang; Junghyun Nam; Moonseong Kim; Kim-Kwang Raymond Choo (The Scientific World Journal)
We revisit the SM2 protocol, which is widely used in Chinese commercial applications and by Chinese government agencies. Although it is by now standard practice for protocol designers to provide security proofs in widely accepted security models in order to assure protocol implementers of their security properties, the SM2 protocol does not have a proof of security. In this paper, we prove the security of the SM2 protocol in the widely accepted indistinguishability-based Bellare-Rogaway model under the elliptic curve discrete logarithm problem (ECDLP) assumption. We also present a simplified and more efficient version of the SM2 protocol with an accompanying security proof.